Penerapan Bidang Garapan Manajemen Sarana Dan Prasarana Di SMP Muhammadiyah 1 Medan Terkait “Dampak Lapangan Sekolah Yang Kurang Memadai Terhadap Kegiatan Ekstrakulikuler Dan Pengembangan Potensi Siswa” - Santa Murni A. Situmorang; Theresia Mardiyana Tamba; Santi Theresia Sinurat; Tesa Novia Siburian; Daniel Fransisto Hutabarat; Miming Kartika Olivia Silitonga (Journal of Creative Student Research, 2024)
This research aims to explore in depth the problems related to facilities and infrastructure as well as follow-up programs in the field of student management at SMP Muhammadiyah 1 Medan. This research uses qualitative research with a descriptive approach. Qualitative research is research that is descriptive in nature and tends to use analysis. The results of this research show that the implementation of the Facilities and Infrastructure Development Sector is related to the problem of inadequate fields at SMP 1 Muhammadiyah, the author can draw the conclusion that student extracurricular activities are really needed in developing students' talents. Inadequate fields can affect students' extracurricular limitations, for example in the field of sports. The management of facilities and infrastructure at SMP I Muhammadiyah is said to be good, however, field facilities that are inadequate need to focus on development to make them better.